Osteogenesis Imperfecta Presented with Vertebral Fractures After Pregnancy and Treatment with Cyclical Etidronate: A Case Report - Cengiz Bahadır; Özbil Korkmaz; Zerrin Şahin (Galenos Yayinevi, 2005)
Osteogenesis imperfecta(OI) is a kongenital skelatal disorder charecterized by low bone mass and increased bone fragility. Fractures due to increased bone fragility occur frequently in childhood and decrease with age. Only a few studies have been reported regarding the teratment of adult patients with OI. Our case was a 27 year old woman with severe back pain occured when she was lifting her baby. The patient had experienced multiple fractures of long bones by her childhood. Compression fractures at thoracal 10 and 12 vertebrae were found on Magnetic Resonance Imaging . Dual energy X-ray absorptiomety(DEXA) showed that markedly decreased bone mineral density(BMD) both at lumbar spine and femur. The diagnosis of OI type I was based on the findings of blue sclera, antecedent multiple fractures, positive family history and low bone mass. Patient was treated with cyclical etidronate, calcium and Vitamin D over a year. No new fractures were observed during the treatment period. Lomber and proximal femur BMD's were found to be significantly increased at the end of one year. Our case was treated succesfully with combination of cyclical etidronate, calcium and vitamin D. Etidronate would seem to be available treatment for adult patients with OI. However, the best treatment regimen and the long-term outcomes of etidronate therapy are unknown.